2024
DOI: 10.1039/d3sc05974j
|View full text |Cite
|
Sign up to set email alerts
|

Unusual catalytic strategy by non-heme Fe(ii)/2-oxoglutarate-dependent aspartyl hydroxylase AspH

Anandhu Krishnan,
Sodiq O. Waheed,
Ann Varghese
et al.

Abstract: Biocatalytic C-H oxidation reactions are of important synthetic utility, provide a sustainable route for selective synthesis of important organic molecules, and are an integral part of fundamental cell processes. The...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 236 publications
0
3
0
Order By: Relevance
“…23−37 Similarly, mutations of second and outer coordination sphere residues have advanced our understanding of 2OG oxygenase catalysis. 38 However, performing structure−function relationships to probe the role of the conserved bis-histidine coordination environment has proven challenging, as mutation of either of the cis-disposed ligands abolishes catalytic function. If we were able to make functional ligand replacements, we could begin to address important questions such as the effect of ligand strength on Fe IV �O reactivity or positioning ("in-line" vs "offline" 39,40 ) across family members.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23−37 Similarly, mutations of second and outer coordination sphere residues have advanced our understanding of 2OG oxygenase catalysis. 38 However, performing structure−function relationships to probe the role of the conserved bis-histidine coordination environment has proven challenging, as mutation of either of the cis-disposed ligands abolishes catalytic function. If we were able to make functional ligand replacements, we could begin to address important questions such as the effect of ligand strength on Fe IV �O reactivity or positioning ("in-line" vs "offline" 39,40 ) across family members.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Given the broad array of valuable transformations catalyzed by 2OG oxygenases, there is considerable interest in understanding how their active site features govern the structure and reactivity of catalytic intermediates. To this end, a range of spectroscopic, kinetic, structural, and computational studies have advanced our understanding of the 2OG oxygenase catalytic cycles. Similarly, mutations of second and outer coordination sphere residues have advanced our understanding of 2OG oxygenase catalysis . However, performing structure–function relationships to probe the role of the conserved bis-histidine coordination environment has proven challenging, as mutation of either of the cis-disposed ligands abolishes catalytic function.…”
Section: Introductionmentioning
confidence: 99%
“…A serials of recent studies conducted by Schofield et al profoundly revealed how the enzyme protein environment and the structure of the substrate interactively regulate the function of the enzyme. 25–28 Investigation of the catalytic rearrangement reaction mechanism of THP by BBOX at the molecular level potentially not only provides deeper and newer insights into the 2OG enzyme family but also broadens our understanding of radical-based enzymatic catalysis.…”
Section: Introductionmentioning
confidence: 99%